Dal Mythos al Logos. Genealogia della Pedagogical Turn - Viviana Segreto (Firenze University Press, 2013)
It is possible to identify an original pedagogical turn starting from classical world, when the theoretical thinking and the organization of a shared public space involve in the constitution of pedagogical science, which must found an educational model useful in the new theoretical and political context. The turning point is located in the devaluation of religious-mythical education, thinking image as false, and in the founding of the paradigm of identity, based on word as true.